MASALAH KETIMPANGAN PENDAPATAN DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Samosir, Yosafat Renovaldo; Remus Silalahi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the factors causing income inequality in Indonesia and its impact on national economic growth. The research employs a descriptive qualitative approach through literature study from various scientific sources and secondary data, including publications from the Indonesian Central Bureau of Statistics (BPS). The findings reveal that income inequality in Indonesia is driven by three main factors: first, disparities in access to quality education between urban and rural areas, creating gaps in workforce skills and productivity; second, unequal access to productive capital such as land, bank credit, and technology, which reinforces economic concentration among specific groups; third, imbalanced regional development, particularly between Java and outer islands, causing infrastructure gaps and unequal economic opportunities. The impact of this inequality on economic growth is significant, including limited domestic consumption due to low purchasing power, hindered investment and innovation due to underdeveloped markets, and increased risk of social instability disrupting the business climate. Although some perspectives suggest inequality can stimulate short-term growth through investment accumulation, this study confirms that in the long term, high inequality becomes a major obstacle to sustainable economic development. The policy implications emphasize the importance of equitable access to education and healthcare, strengthening financial inclusion, balanced infrastructure development, and progressive taxation systems combined with targeted social assistance programs to create inclusive and equitable economic growth.